Vegetation community development on a chronosequence of abandoned gold and rehabilitated nickel tailings around the Great Dyke region in Zimbabwe - Nyenda, Tatenda (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDConsEcol)--Stellenbosch University, 2020.